(3cJGH GdChdjGAs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s
(3ChdgG (B:s
(3MOKfG GdTjN GdEeGe Ydi GdOjf CHh GdMSjf CMeO Hf MeRg Hf Ydi s
(3fSNI eUhQI Yf fSNI GdeOQSI GdCMeOjI ai LGeY CMeO HGTG GdLRGQ HYcGs
(3GfXQg HQbe (B352 (3JUhas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B153 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B209 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs